The "Warm Houses" program: Insulating existing buildings through compulsory retrofits. (March 2015) - Lo, Kevin
Abstract: The importance of insulating the existing building stock in the age of climate change and energy scarcity is well recognized, but effective public policies for doing so have not been forthcoming. This paper analyzes a novel approach pioneered by the city of Changchun in northeast China. Since 2010, the municipal authority has implemented a program to refurbish nearly half a million homes with wall and roof insulation and energy-efficient windows and doors. The success of this program is attributed to an assertive approach and an efficient, government-sponsored funding model. However, the program faces several challenges, including a lack of effective supervision, the negative impact on poor households, and ineffective energy-saving due to a lack of progress in heat-metering reform. This paper concludes by discussing the policy implications of this analysis.